Formulation and evaluation of herbal tablet from moringa Oleifera leaves (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
The aim of the study is formulation and evaluation of herbal tablets from moringa oleifera leaves. Moringa oleifera leaves was extracted with ethanol and formulated by using different binders which included Gelatin, Micro-crystalline Cellulose (MCC), Maize Starch produced the best tablets of ethanol extract of Moringa oleifera leaves. Numerous criteria, including strength (friability, crushing strength), and release characteristics (disintegration and dissolution durations tests), were used to characterize the formulations. The outcome demonstrated that, in comparison to tablets made with MCC or maize starch, those made with gelatin as a binder had the lowest friability and disintegration time.